What do digital inclusion and data literacy mean today? - Elinor Carmi; Simeon J. Yates (Internet Policy Review, 2020)
As more of our everyday lives become digital, it has become crucial to include everyone in the digital society. This special issue is examining the different layers of digital inclusion and data literacy by drawing on research, policy, and practice developments around literacies in various regions and contexts. It highlights the politics around them so as to propose policies that are needed to include more people in datafied societies, and what types of literacies they should learn. This issue includes three commentaries by experts in the field and five peer-reviewed academic papers that go towards tackling digital inclusion. This means to find solutions to the fact that many people are left behind technological advancements, and that these create what is commonly called - the digital divide.
Keywords: 300; Digital inclusion; Data literacy